Proximal aortic arch cannulation for proximal ascending aortic aneurysms - Emrecan, Bilgin; Durna, Fýrat; Girgin, Serkan; Alshalaldeh, Mohammed (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: Different arterial inflow sites have been reported to date for particularly challenging cardiac operations. The ascending aorta, femoral artery, and subclavian artery are the most commonly used sites. Although its use has been reported, the aortic arch has not gained popularity in the performance of cannulation. According to a search performed in the PubMed database, aortic arch cannulation for ascending aorta replacement has not been examined in a separate study before. In the present study, we report the treatment outcomes of patients with ascending aortic aneurysms in whom the aortic arch was cannulated for arterial inflow. Material and methods: Twenty-seven patients with aneurysmal dilatation of the ascending aorta underwent ascending aorta replacement from April 2010 to March 2013. The mean age of the patients was 64 years. All operations were carried out by cannulating the aortic arch distally from the origin of the innominate artery. Results : There was no mortality or cannulation-related morbidity. In 23 patients, only the supracoronary ascending aorta was replaced, whereas in 4 patients, the button modification of the Bentall procedure was performed to replace the root and the ascending aorta. Conclusions: The technique of aortic arch cannulation distal to the origin of the innominate artery is worthy of consideration in the treatment of aneurysms limited to the ascending aorta due to its safety, simplicity, and low morbidity.